CONSISE statement on the Reporting of Seroepidemiologic Studies for Influenza (ROSES-I statement): an extension of the STROBE statement - Horby, P; Laurie, K; Cowling, B; Engelhardt, O; Sturm-Ramirez, K; Sanchez, J; Katz, J; Uyeki, T; Wood, J; van Kerkhove, M; Committee, C (Wiley, 2016)
Background Population-based serologic studies are a vital tool for understanding the epidemiology of influenza and other respiratory viruses, including the early assessment of the transmissibility and severity of the 2009 influenza pandemic, and MERS-CoV. However, interpretation of the results of serologic studies have been hampered by the diversity of approaches and the lack of standardized methods and reporting. Objective The objective of the CONSISE ROSES-I statement is to improve the quality and transparency of reporting of influenza seroepidemiologic studies and facilitate assessment of the validity and generalizability of published results. Methods The ROSESI statement was developed as an expert consensus of the CONSISE epidemiology and laboratory working groups. The recommendations are presented in the familiar format of a reporting guideline. Since seroepidemiologic studies are a specific type of observational epidemiology study, the ROSESI statement is built upon the STROBE guidelines. As such the ROSESI statement should be seen as an extension of the STROBE guidelines. Results The ROSES-I statement presents 42 items that can be used as a checklist of the information that should be included in the results of published seroepidemiologic studies, and which can also serve as a guide to the items that need to be considered during study design and implementation. Conclusions We hope that the ROSES-I Statement will contribute to improving the quality of reporting of seroepidemiologic studies.